Strengthening the Tourism Sector Business in Gorontalo Province Through the Utilization of The E-Commerce Platform and The Electronic Word of Mouth - Monoarfa, Valentina; B Biki, Syamsul; Widiani, Komang; R. Hasan , Fatriansyah (Technium Social Sciences Journal, 2021)
This study was conducted to analyze the role or influence between e-commerce platforms, electronic word of mouth on the business performance of the tourism sector in several tourist attractions in Gorontalo. The design of this research was a mix method, where some of the objects of this research were visitors and residents around the tourist attractions amount 30 people. The data analysis that we used were hypothesis testing, validity, reliability, normality and multiple regression as well as interviews as additional research information. The results show that E-commerce has an influence on tourism performance, and E-WOT does not have a significant relationship with tourism business performance in Gorontalo.